Byron and romanticism - McGann, Jerome J (Cambridge University, 2013)
This collection represents twenty-five years of work by Jerome McGann, one of the most important critics of Romanticism and Byron studies. Many of these essays have previously been available only in specialist scholarly journals. Now McGann's influential work on Byron can be appreciated more widely by new generations of students and scholars.